ANALISIS KEBIJAKAN PENDIDIKAN BERDASARKAN ASPEK SARANA DAN PRASARANA - Hindarsyah, Eka Wahyu; Nazir, Nazir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education plays a major role in the development of a country, and the quality of educational facilities and infrastructure plays an important role in the teaching and learning process. The aim of this research is to analyze the management of educational facilities and infrastructure in schools. The author's focus aims to describe the facilities and infrastructure in education. This research method is literature study and bibliographic analysis using Publish or Perish, Google Scholar and digital libraries. It is hoped that this research can contribute to a deeper understanding of how the management of educational facilities and infrastructure in schools can influence the quality of learning. Thus, this research can be a basis for formulating more effective policies in managing educational facilities and infrastructure in schools with the ultimate aim of improving the overall quality of education.